Influences of Indonesian coals on the performance of a coal-fired power plant with an integrated post combustion CO2 removal system: A comparative simulation study - Saptoro, Agus; Huo, Kong (Elsevier Science Limited, 2013)
The process of electric power generation from coal with and without post-combustion CO2 capture system was simulated using Aspen HYSIS ® flowsheet simulation. The simulated plant was used to investigate the effects of different ranks of Indonesian coals on CO2 emission and plant efficiency. Simulation results on the plant efficiency penalties are agreeable with the existing studies on coal-fired power plant with an integrated CO2 capture in Indonesia, China, Australia, US and most of Organization for Economic Co-operation and Development (OECD) countries. The results also indicated that the ideal fuel for power generation is anthracite since it results in the least CO2 emission and efficiency penalty. However, due to abundant reserves of lignite and sub-bituminous, most of Indonesian power plants are fuelled with these types of coals. Therefore, more efforts should be directed to minimize efficiency penalty by improving the CO2 capture systems either by using more efficient solvents or minimizing the energy usage in solvent regeneration or both.